Quantifying Sediment Transport in La Estrella River, Limón, Costa Rica - Cervantes-Córdoba, Andrés (2016)
The growing need of water resources for different uses, in nature and in human activities has stimulated and increased the detailed study of the stages of the water cycle. Costa Rica is a country with many rivers throughout its area, which is located in the tropics and where it rains significantly throughout the year. This means that most of the rivers raise their water flow significantly, causing loss or damage of civil infrastructure and problems in extensive agricultural areas. Specifically, La Estrella River overflows have caused serious damage, to nearby plantations and affected people from nearby villages. The objective of this study is to determine the hydraulic capacity of La Estrella River to transport sediment. To do this a stepwise methodology was used. This involved several trips to the study site in order to collect sediment samples and flow rate measurements at different locations of the river. The sediment samples were subsequently analyzed in the laboratory. Finally, sediment transport calculations were performed by means of various theoretical equations. The result, values of the amount of sediment that the river can transport under similar conditions to those founded in the field trips.